The Effects of Declining Fertility on Household Socioeconomic Conditions in Tanzania: A Comparative Study of Urban versus Rural Areas of Kwimba District, Mwanza Region. (23rd August 2016) - Masanja, George Felix; Lwankomezi, Emmanuel; Emmanuel, Chrisant
Abstract : This study examined the effects of declining fertility on household socioeconomic and health conditions in Tanzania, using a comparative survey of urban versus rural areas of Kwimba District in Mwanza region. Cross-sectional cum causal-comparative research design was adopted for the study. The target population is comprised of all females of the childbearing age residing in Kwimba District. The study utilized a stratified random sampling technique to pick two areas in the district while disproportionate random sampling technique was used to select 196 respondents. A questionnaire was used to elicit information from the respondents. Multivariate analyses were adopted to answer the three research questions of the study. The findings of this study revealed that women of the childbearing age from the two study sites in the district exhibited a small difference regarding fertility inequalities and socioeconomic and health conditions. This study also discovered a significant relationship between critical socioeconomic variables and women's improved socioeconomic status in the communities. These findings, therefore, provide an explanation for the onset of fertility decline which has consequently led to some demonstrated demographic dividend at a household level. The paper recommends enhancement of social transformation and women empowerment in both rural and urban environments for sustained improved living conditions.